Dampak La Nina 2020 – 2021 Terhadap Curah Hujan di Sulawesi Tenggara - Siti Risnayah (Buletin GAW Bariri, 2021)
To determine the effect of La Nina in 2020/2021 on rainfall in Southeast Sulawesi, an analysis of its impact was carried out. 2020 is the year of Moderate La Nina where begins to be active in July when the Southeast Sulawesi region enters the dry season. The data used in this study are rainfall data for 2020-2021, normal data of rainfall and onset season, rainfall anomaly from ITACS, and the Nino3.4 index. Descriptive and statistical analysis methods are used to interpret the graph and describe how La Nina affects rainfall in Southeast Sulawesi. The results showed that La Nina that occurred from 2020 to 2021 was less significant in increasing rainfall in the Southeast Sulawesi region. There are 58% of the research area has decreased rainfall during the La Nina period with an average reduction of 37% from its normal. This rainfall deficit is because the La Nina in 2020/2021 is a La Nina in the Weak to Moderate category so that it is less significant to stimulate an increasing rainfall. La Nina also had less impact on the 2020 dry season in Southeast Sulawesi but had quite impactful on advancing the onset of the rainy season. That is because, during the dry season, La Nina is still in the Weak category. La Nina begins to strengthen in the October-November-December period so that the rainy season generally begins in November.